ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2013 - Taufik, Taufeni; Sofyan, Azhari; ', Ariyadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aimed to significantly influence the business risk , asset structure , Profitability, Size of the company affect the Capital structure of Basic industry and chemicals companies are listed at Indonesia Stock Exchange for period from 2011 until 2013. The Model which used in this research is multiple linear regression. Data was obtain from 37 Basic industry and chemicals companies as the sample in research in Indonesian Stock Exchange during the period of 2 years in a row. The data is processed by using SPSS for windows version 16.0. The results of this research can be concluded that the business risk, Profitability, the size company effect on Capital structure. Of the t test results obtained Business risk value t count (4,369 ) > t tabel(1,980), Profitability t count (2,323 ) > t tabel(1,980), Size companies t count (2,306 ) > t tabel(1,980), and significantly below the 0,05 level P value (0,000). While Asset structure has no significant effect with the t test results obtained t count (1,134 ) < t tabel(1,980) and significantly above the 0,05 level P value(0,191) on Capital structure of Basic industry and chemicals companies are listed at Indonesia Stock Exchange for period from 2011 until 2013.Keywords : Business risk, Asset structure, Profitability, Size companies, and Capital structure.